Peningkatan Kemandirian Belajar Siswa SMK pada Mata Diklat Teknologi Mekanik dengan Metode Problem Based Learning - FX Wastono (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
The objective of the study was to improve the students’ learning independence for the subject of Mechanical Technology through Problem Based Learning. This study was categorized as a classroom action research. The subjects of study were the teacher and the grade X students of the Mechanical Engineering Department at SMK Negeri Kulon Progo. The data collection techniques used tests, observation and documentation. The validity of the study was proven by triangulation. The data analysis technique was qualitative descriptive. The results of the study revealed an improvement of the students’ learning independence indicated by (1) the scores of the test satisfying the minimum mastery criterion increased from 25% to 70% (2) the increase of the students’ responsibility from 37% to 72% (3) The increase of the students’ learning discipline from 32% to 67% (4) The increase of the students ‘creativity and activeness from 14% to 65%. It is noted that Problem Based Learning can improve the students’ learning independence and achievement.